Influence of Nutritional Status, Physical Activity and Stress Level on Menstrual Cycle - Sindi Laras Wari; Masryna Siagian; Herbert Wau (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Menstrual cycle research was conducted on female students of the Public Health Study Program of Prima Indonesia University because it was found that 53% of female students experienced abnormal menstrual cycles. Irregular menstrual cycles can be an indicator of reproductive health issues such as hormonal imbalances or other endocrine disorders. This study was to see the relationship between nutritional status, physical activity and stress levels with the menstrual cycle in female students of the Public Health Study Program of Prima Indonesia University. This type of research uses analytical observational using cross-sectional design. The population in this study was 204, with 135 samples obtained by random sampling technique. Data analysis was carried out using the chi-square statistical test and multivariate logistic regression binomial. Most of the subjects experienced normal nutritional status by 63%, light physical activity by 49.6%, moderate stress level by 83% and abnormal menstrual cycle (oligomenorrhea menstrual cycle > 35 days) by (60%). There was no relationship between nutritional status (p=0.650) and physical activity (p=0.528) with menstrual cycle. There was an association between stress level (p=0.043) with menstrual cycle. Thus, nutritional status and physical activity did not correlate with the menstrual cycle, but stress level correlated with menstrual cycle of students. Based on the research findings, it is recommended to implement stress control programs and increase awareness about the menstrual cycle for female students.